The Phenomenon of Bilingualism in Udmurt Literature (on the Example of G. E. Vereshchagin's Works) - Alevtina V. Kamitova (Publishing house "Sreda", 2022)
The article describes the phenomenon of bilingualism, expressed in Udmurt literature at the origins of its formation. An analytical insight of this phenomenon is undertaken on the example of the works of the first Udmurt writer G. E. Vereshchagin, namely, on one of his poems. The introductory part briefly describes the various possible forms of a writer's bilingualism, one of which is adopted by the author under study. Several hypothetical versions are proposed to explain the reasons for the Udmurt writer's appeal to self-translation. An analysis of his lullaby "Glaucous, glaucous dovelet!" in Udmurt and its translated version in Russian, carried out by G. E. Vereshchagin himself, is provided. In the course of a comparative study, similarities and differences were found. It is summarized that the formation of a bilingual context in Udmurt literature begins with the works of G. E. Vereshchagin. Through the author's translation, his poetic creativity is also presented to the Russian-speaking reader for the first time. It is revealed that in the translated text the poet successfully embodied the national stylistics and figurative expressiveness inherent in the original. The study of the bilingual creativity of G. E. Vereshchagin contributes to the understanding of the bilingual phenomenon of national literature.